Numerical and Theoretical Analyses of Laminated Veneer Lumber Beams Strengthened with Fiber-Reinforced Polymer Sheets - Michał Marcin Bakalarz; Paweł Grzegorz Kossakowski (Applied Sciences, 2024)
This study outlines a method of utilizing the finite element method and a simple mathematical model to predict the behavior of laminated veneer lumber (LVL) beams strengthened with composite sheets. The numerical models were created using the Abaqus 2017 software. The LVL was considered as a linearly elastic or elastic–plastic material, factoring in Hill’s yield criterion. The composites were simulated as linearly elastic–ideally plastic materials. The mathematical models were predicated on the methodology of transformed cross-section. The theoretical and numerical outcomes were juxtaposed with previous empirical investigations. The comparison encompassed load-bearing capacity, stiffness, and deformation under peak force. Furthermore, presentations of normal stress maps in the LVL and composite have been illustrated. The derived maps were juxtaposed with the delineations of failure modes. An adequate correlation was identified between the theoretical, numerical, and empirical values in the case of beams reinforced with aramid, glass, and carbon sheets. The relative deviation varied from several to multiple percentages. This technique is not applicable for evaluating load-bearing capacity and deformation when only dealing with sheets with low elongation of rupture. This is a consequence of their premature failure. The proposed models may be utilized by researchers and engineers in the design of reinforcements for timber structures.